Aprendendo com os Guaranis a resistir e sonhar com terras livres - Oliveira, Ana Lucia de Castro (2020)
This research tried to build dialogue and approximations with the Guarani worldview. It was financed by CAPES during its development, wich made the resarch possible. It sought to understand the paths of the civilization crisis that we are going through, the unfolding, the problems and the way out to other ways of living Through the construction of intercultural dialogue, it identified that the worldview of the Guarani people is a source of inspiration in what they conceive of resistance when cultivating their customs - their culture in their existential territory - at Tekoha for thousands of years.We can affirm that the paths and strategies of the Guarani people, in the creation of a coming to be directed to preserve life, indicating an active micropolitics as an ethical compass that gives meaning on where to go, alleges Teko Porã - the beautiful life, admiring the creation of Nhanderu, dreaming of Yvy Rupa- Earth as one, free lands can help us to reaffirm utopias and to reinvent the civilizational model in crisis. The power of the encounter and what we can learn from the original peoples has shown us the relevance of the wisdom shared by these peoples and the urgency to emerge this knowledge in contemporary society.